(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
Financial accounting is crucial for businesses as it enables them to make well-informed decisions that are aligned with their objectives. The accuracy of financial information is vital for budgeting, forecasting, and compliance with regulations. Furthermore, it aids in evaluating performance, identifying financial risks, and providing a foundation for decision-making. In essence, financial accounting is indispensable in ensuring that businesses make financially viable decisions that do not jeopardize their operations. Without accurate financial information, businesses may make decisions that put them at risk.